Distribution of autochthonous dendro-species in the Management Unit „Ozren“-Petrovo – implementation of GIS technology - Đorđije Milanović; Vladimir Stupar; Jugoslav Brujić; Davor Nikić (Glasnik Šumarskog Fakulteta Univerziteta u Banjoj Luci)
The paper shows the distribution of autochthonous dendro-species in the Management unit „Ozren“ of the Forest office „Petrovo“ in the northern Bosnia. Species were mapped using the GIS technology, with the square network 1x1 km, which was laid into the National Cartesian coordinate system, in zone 6. In the total of 109 squares, 93 species of trees and shrubs were recorded. Using the GIS software the spatial database was made, which as the main output gave the distribution maps of those species in the research area. This work should contribute to the knowledge of the horology of dendrospecies in Bosnia and Herzegovina, as well as to start the unique database, which would, using the method proposed, be filled up by data on distribution of dendro-species in this country.